Organization Of Education Of Traffic Rules To Pupils In A Digitalization Environment Through Modern Technologies - Jumayev Yunus Rashidovich (Genius Journals, 2025)
This article discusses methods for increasing the effectiveness of education by teaching traffic rules to small groups of students of preschool educational organizations in a digitalization environment through modern digital technologies
Keywords: modern technologies; traffic rules